2014
DOI: 10.1371/journal.pone.0108320
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Brain Magnetic Resonance Imaging Study of Neuromyelitis Optica Spectrum Disorder

Abstract: Brain involvement is commonly seen in patients with neuromyelitis optica spectrum disorder (NMOSD). However, little is known about the chronic changes of acute brain lesions on MRI over time. Here, our objective was to evaluate how acute brain MRI lesions in NMOSD changed on follow-up MRI. We reviewed the MRIs of 63 patients with NMOSD who had acute brain lesions and follow-up MRI over an interval of at least 3 months. Of the 211 acute brain lesions, 24% of lesions disappeared completely on T2-weighed images (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 38 publications
(45 reference statements)
1
32
1
1
Order By: Relevance
“…We did not focus on the distribution of the T2-hyperintense lesions, and thus the effects of T2-hyperintense lesions on the focal FA values was not excluded. However, recent MRI studies showed that, as opposed to MS lesions, NMO lesions in the brain were nearly absent in the basal ganglia and cortical regions (Kim et al, 2014;Kister et al, 2013;Sinnecker et al, 2012). These results may indicate that the change of thalamic microstructure in NMOSD patients is derived from the secondary condition of disease rather than from the direct interference.…”
Section: Discussionmentioning
confidence: 90%
“…We did not focus on the distribution of the T2-hyperintense lesions, and thus the effects of T2-hyperintense lesions on the focal FA values was not excluded. However, recent MRI studies showed that, as opposed to MS lesions, NMO lesions in the brain were nearly absent in the basal ganglia and cortical regions (Kim et al, 2014;Kister et al, 2013;Sinnecker et al, 2012). These results may indicate that the change of thalamic microstructure in NMOSD patients is derived from the secondary condition of disease rather than from the direct interference.…”
Section: Discussionmentioning
confidence: 90%
“…Many autoimmune disorders in the pediatric population can affect the basal ganglia, including post-streptococcal autoimmunity [39], N-methyl-D-aspartate receptor (NMDAR) antibodies [40], neuromyelitis optica (NMO)/neuromyelitis optica spectrum disorders (NMOSD) [41], and ADEM ( Fig. 6) [42].…”
Section: Autoimmunitymentioning
confidence: 99%
“…Central nervous system involvement beyond the optic nerves and spinal cord is still compatible with NMO [51], although in fairness, this would be an uncommon presentation. T2 hyperintense lesions may affect the basal ganglia (and are characteristically Bblurred^), hypothalamus, white matter (more frequently the frontal lobes), corpus callosum, periventricular and periaqueductal regions, [41]. Interestingly, basal ganglia lesions may resolve completely over time [41].…”
Section: Pediatric Autoimmune Neuropsychiatric Disorders Associated Wmentioning
confidence: 99%
See 2 more Smart Citations